ANALISIS PENGUASAAN KOSAKATA BAHASA MANDARIN PADA SISWA KELAS 10 SMK IMMANUEL II SUNGAI RAYA - Felisia Felisia; Tjen Veronica; Suhardi Suhardi (Universitas Tanjungpura, 2022)
Chinese has become the most popular foreign language for people in the world to learn at the moment. As we all know, mastering Chinese vocabulary is one of the hardships in the process of learning Chinese, especially for second-language learners from Latin alphabet countries such as Indonesia. Therefore, the writer decided to conduct research at Immanuel High School. In order to understand the mastery and difficulties of first-year students of Immanuel High School, this paper uses the literature research method and the test research method to conduct research. The test results showed that the student’s mastery of Chinese vocabulary was 84.2%. The accuracy rate of